2014
DOI: 10.1007/s10894-014-9823-1
|View full text |Cite
|
Sign up to set email alerts
|

Calculations of Double-Differential Neutron Emission Cross Sections for 9Be Target Nucleus at 14.2 MeV Neutron Energy

Abstract: In this study, we investigated neutron-emission spectra induced by (n,xn) nuclear reactions for the 9 Be structural fusion material at 14.2 MeV neutron energy. We calculated double-differential cross sections ( d 2 r dXde ) with ALICE-2011 codeor the angles of 30°, 60°, 90°, 120°, and 150°. Hybrid Monte Carlo simulation model have been used to calculate the double differential emission spectra for these different angles. The obtained results were compared with the measured data taken from EXFOR library. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 24 publications
0
5
0
1
Order By: Relevance
“…Full exciton model calculations have been done with PCROSS code [27] that used the initial exciton number as n o =1 of 1 neutron and 0 hole [10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Theoretical calculations of 10 B(p,α) equilibrium and pre-equilibrium reactions are compatible with each other as seen in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Full exciton model calculations have been done with PCROSS code [27] that used the initial exciton number as n o =1 of 1 neutron and 0 hole [10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Theoretical calculations of 10 B(p,α) equilibrium and pre-equilibrium reactions are compatible with each other as seen in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The empirical cross section formula is including proton inelastic cross section and Coulomb effects of reactions induced by proton can be expressed suggested in many studies [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] as follows:…”
Section: Methodsmentioning
confidence: 99%
“…Tel et al [5] suggested that the empirical cross section formulae including proton inelastic cross section [13][14][15][16] and Coulomb effects of reactions induced by proton can be expressed as follows,…”
Section: Calculation Model and Methodsmentioning
confidence: 99%
“…Bu yüzden; deney yapmanın mümkün olmadığı durumlarda, bu verilerin hesaplama ve benzetim programları yardımıyla elde edilmesi gerekir. Bu yüzden, araştırmacılar fisyon ve füzyon reaktörlerinde kullanılan malzemelerin tesir kesitlerini ve reaksiyon sonucu açığa çıkan parçacıkların enerji spektrumlarını bilgisayar kodları yardımı ile hesaplamaktadırlar [6][7][8][9][10][11]. Bu çalışmada; füzyon reaktör malzemelerinde kullanılan 27 Al, 56 Fe, 58 Ni ve 90 Zr elementler için (p,x 3 He) reaksiyonu sonucunda elde edilen 3 He yayınlanma spektrumları incelenmiştir.…”
Section: Introductionunclassified